Step advancement flap technique of ear lobe repair - M. O., Harish; R., Chethana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Ear piercing and ornament wearing is a historical tradition. Dilated ear lobe and torn earlobe usually results from sudden trauma or continuous use of heavy earrings. Various surgical techniques have been described for the correction of the same. Each procedure has its own pros and cons. The choice will depend on individual preferences and the defect, partial or total, and should offer a lower chance of recurrence. The corrections can be made with or without preservation of the earring orifice. The aim and objectives of this study was to present and discuss a novel technique of repairing the partial and complete cleft ear practiced at Karwar Institute of Medical Sciences Hospital, Karnataka, India. Methods: A prospective study was done on the use of a novel technique “Step advancement flap” in the repair of partial and complete cleft ear lobe in 18 patients. Results: A good post-operative results were achieved in all the patients with maintained ear lobe thickness and a sutured skin scar away from the center. Conclusions: Our technique has an advantage of maintaining the normal ear lobe thickness and the sutured skin scar away from the center on either side of the ear lobule compared to other techniques. Thus the neo piercing can be done at a fresh central skin avoiding the skin scar.